Effectiveness and its mechanism of chrysophanic acid for aortic calcification with diabetic nephropathy based on the Notch1-RBP-Jk/Msx2 signaling pathway - DUAN Xiao-xing; CHANG Yong-li; ZHANG Guo-guang; PAN Xue (Linchuang shenzangbing zazhi)
Objective To explore the effectiveness of chrysophanic acid for aortic calcification in diabetic nephropathy based on the Notch1-recombining binding protein suppressor of hairless(Notch1-RBP-Jk)/Msx2 signaling pathway. Methods Forty adult SD rats were selected and 32 were used to establish the model of aortic calcification with diabetic nephropathy and randomly divided into 4 groups(model control group, low-dose group, middle-dose group and high-dose group). The remaining 8 rats were recorded as normal control group. The rats in the low, medium and high dose groups were administered gastrically with 50 mg/kg, 100 mg/kg and 150 mg/kg chrysophanic acid respectively; and the rats in the model control and normal control groups were given the same amount of saline, once a day for 4 weeks. Renal function changes before and after intervention were compared. After intervention, the rats in each group were sacrificed, and the abdominal aorta was taken to observe the calcification. The calcium contents in abdominal aorta tissues were detected. RT-PCR was used to detect the expressions of Notch1, RBP-JK, Msx2, α-SMA(α-smooth muscle actin) and Runt-related transcription factor 2(Runx2) mRNA in the abdominal aorta of each group. The related expressions of Notch1, RBP-JK, Msx2, α-SMA and Runx2 proteins in abdominal aorta tissues were detected by Western blotting. Results Compared to the model control group, in the three dose groups, after intervention the renal function indexes were improved, abdominal aortic calcification was alleviated and calcium content in abdominal aortic tissues was reduced. The expressions of Notch1, RBP-JK, Msx2, Runx2 and protein in the three dose groups were all decreased, while the expression of α-SMA and protein were increased. Among the three dose groups, in the high dose group various indices were improved best. Conclusions Chrysophanic acid can protect renal function and reduce calcification in diabetic aortic calcification rats, and it is expected that its mechanism may relate to down-regulation of Notch1, RBP-JK, Msx2, Runx2 mRNA and protein expressions, and up-regulation of α-SMA mRNA and protein expressions.